Optimization of preparation conditions and in vitro sustained-release evaluation of a novel nanoemulsion encapsulating unsaturated guluronate oligosaccharide. (15th July 2021) - Li, Meiting; Bi, Decheng; Yao, Lijun; Yi, Jiang; Fang, Weishan; Wu, Yan; Xu, Hong; Hu, Zhangli; Xu, Xu
Graphical abstract: Highlights: A novel unsaturated guluronate oligosaccharide (GOS)-based W1/O/W2 nanoemulsion was successfully prepared. The average particle size and centrifugal stability of the optimal nanoemulsion were 273.93 nm and 91.37 %, respectively. The GOS nanoemulsion was shown to be a steady delivery system for the slow release of GOS. Abstract: Unsaturated guluronate oligosaccharide (GOS) was prepared from alginate-derived homopolymeric blocks of guluronic acid by alginate lyase-mediated depolymerization. In this study, a GOS-based water-in-oil-in-water (W1/O/W2) nanoemulsion was prepared, and different influencing factors were investigated. First, linseed oil was selected as the optimal carrier oil. Then, other optimal conditions of the GOS nanoemulsion were determined based on response surface methodology (RSM). Under the optimal conditions, the obtained GOS nanoemulsion showed a spherical structure with an average particle size of 273.93 ± 8.91 nm, and its centrifugal stability was 91.37 ± 0.45 %. Moreover, the GOS nanoemulsion could achieve the aim of sustained release in vitro and be stably stored at 4°C for at least 5 days. This work prepared a novel GOS-based W1/O/W2 nanoemulsion that may effectively address the storage difficulties of unsaturated GOS and provides a valuable contribution to the application of GOS in the food and medicine fields.